The assessment of Pseudomonas aeruginosa lectin LecA binding characteristics of divalent galactosides using multiple techniques. (10th July 2021) - Zaree, Pouya; Sastre Torano, Javier; de Haan, Cornelis A M; Scheltema, Richard A; Barendregt, Arjan; Thijssen, Vito; Yu, Guangyun; Flesch, Frits; Pieters, Roland J
Abstract: Pseudomonas aeruginosa is a widespread opportunistic pathogen that is capable of colonizing various human tissues and is resistant to many antibiotics. LecA is a galactose binding tetrameric lectin involved in adhesion, infection and biofilm formation. This study reports on the binding characteristics of mono- and divalent (chelating) ligands to LecA using different techniques. These techniques include affinity capillary electrophoresis, bio-layer interferometry, native mass spectrometry and a thermal shift assay. Aspects of focus include: affinity, selectivity, binding kinetics and residence time. The affinity of a divalent ligand was determined to be in the low-nanomolar range for all of the used techniques and with a ligand residence time of approximately 7 h, while no strong binding was seen to related lectin tetramers. Each of the used techniques provides a unique and complementary insight into the chelation based binding mode of the divalent ligand to the LecA tetramer.